Chemistry of hydroperoxycarbonyls in secondary organic aerosol. Issue 10 (3rd October 2018) - Pagonis, Demetrios; Ziemann, Paul J.
Abstract: Highly oxidized multifunctional compounds (HOMs) formed through gas-phase reactions are thought to account for a significant fraction of the secondary organic aerosol (SOA) formed in low-nitric oxide (NO) environments. HOMs are known to be peroxide-rich and unstable in SOA, however, and their fate once they partition into particles is not well understood. In the study reported here, we identified particle-phase reactions and decomposition products for an α-alkoxy hydroperoxyaldehyde that served as a convenient model for HOMs, and also quantified rate and equilibrium constants for cyclic peroxyhemiacetal formation and the effects of particle acidity and relative humidity on reaction products and timescales for decomposition of peroxide-containing compounds. Sulfuric acid increased the rate of acetal formation and subsequent peroxide decomposition, but the effect was eliminated when aqueous seed particles were used in humid air, indicating that organic/aqueous phase separation can affect the ability of strong acids to catalyze these and other reactions in SOA. The results will be useful for understanding and predicting the atmospheric fate of organic peroxides and the effects of their particle-phase reactions on SOA composition. Copyright © 2018 American Association for Aerosol Research